Interpretation of the reasons for judgment in Amos 2.6-16 in the redactional compositions underlying the Amos-text - Hamborg, Graham (2009)
This redaction-critical study interprets the reasons for judgment in Amos 2.6-16 in the literary context of each of the redactional compositions which, I argue, underlie the Amos-text. It is proposed that the Amos-text is both a theological work and a tractate of social criticism. In the earlier redactional compositions the dominant reasons for judgment concern mistreatment of the weak. In the later redactional compositions these are overshadowed, in terms of length of text, by more theological reasons for judgment; however, these strengthen, rather than weaken, the force of the older reasons for judgment.